TRC40 can deliver short secretory proteins to the Sec61 translocon - Johnson, Nicholas; Vilardi, Fabio (Journal of cell science, 2012)
Summary: Whilst the co-translational translocation of nascent proteins across the mammalian endoplasmic reticulum (ER) is well defined, the capacity of this organelle for post-translational translocation is poorly delineated. Here we identify two human secretory protein precursors, apelin and statherin, as bona fide substrates for post-translational translocation across the ER membrane. Further studies, in combination with Hyalophora cecropia preprocecropin A (ppcecA), show that all three proteins bind to TRC40 and can utilise this component for their delivery to the ER membrane in a well-established in vitro system. However, ppcecA is not an obligate TRC40 substrate, and it can also be delivered to the ER by an alternative TRC40-independent pathway. Upon arrival at the ER membrane, these short secretory proteins appear to be ubiquitously transported across the ER membrane through the Sec61 translocon, apparently irrespective of their delivery route. We speculate that the post-translational translocation of secretory proteins in higher eukaryotes is more prevalent than previously acknowledged.